PENINGKATAN KETERAMPILAN PROSES SAINS DENGAN MENGGUNAKAN DISCOVERY LEARNING - simanungkalit, erwin susanto; Sari, Lia Purnama (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2019)
ABSTRACT This study aims to know whether there is a significant improvement of using discovery learning on students’ science process skill on the topic momentum and impulse at the tenth grade students of IPA major of SMA Negeri 1 Kolang. The research was conducted by using descriptive quantitative method with 48 students as the sample and they were taken by using random sampling technique from 74 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the percentage of using discovery learning was 83.6% (good category) and (b) the average of students’ science process skill on the topic momentum and impulse before using discovery learning was 74.6 (good category) and after using discovery learning was 88.19 (very good category). Furthermore, based on inferential statistic, it could be found ttable was less than tcalculated (1.71<16.22). It means, there is a significant improvement of using discovery learning on students’ science process skill on the topic momentum and impulse at the tenth grade students of IPA major of SMA Negeri 1 Kolang. Keywords: discovery learning, science process skill, and momentum and impulse